TIA: A Resource for Those Interested in Educational DevelopmentReview of: <source>To Improve the Academy: Resources for Faculty, Instructional and Organizational Development</source>, Volume 31; <person-group person-group-type="editor"> <name name-style="western"> <surname>Groccia</surname> <given-names>James E.</given-names> </name> <name name-style="western"> <surname>Cruz</surname> <given-names>Laura</given-names> </name> </person-group> (ed); ( <year>2012</year>). <publisher-name>Jossey-Bass Publishers</publisher-name>, <publisher-loc>San Francisco, CA</publisher-loc>. <fpage>400</fpage> pages. - Michael R. Leonardo (American Society for Microbiology, 2013)
Review of: To Improve the Academy: Resources for Faculty, Instructional and Organizational Development, Volume 31; James E. Groccia and Laura Cruz (ed); (2012). Jossey-Bass Publishers, San Francisco, CA. 400 pages.